A specific, nonproliferative role for E2F-5 in choroid plexus function revealed by gene targeting - Lindeman, Geoffrey J. (Cold Spring Harbor Laboratory Press, 1998)
Homozygous E2F-5 knockout embryos and mice have been generated. Although embryonic development appeared normal, newborn mice developed nonobstructive hydrocephalus, suggesting excessive cerebrospinal fluid (CSF) production. Although the CSF-producing choroid plexus displayed normal cellular organization, it contained abundant electron-lucent epithelial cells, consistent with excessive CSF secretory activity. Moreover, E2F-5 CNS expression in normal animals was largely confined to the choroid plexus. Cell cycle kinetics were not perturbed in homozygous knockout embryo fibroblasts. Thus, E2F-5 is not essential for cell proliferation. Rather, it affects the secretory behavior of a differentiated neural tissue.